Implementasi Model Pembelajaran Problem Based Learning untuk Meningkatkan Kemampuan Menganalisis Unsur Intrinsik Cerpen Pada Siswa Kelas XI F 8 SMA Negeri 6 Denpasar - Susrawan, I Nyoman Adi; Wedasuwari, Ida Ayu Made; Kurniawati, Ni Kadek; Adnyana, Pande Putu Bawa (LPPM Institut Pendidikan Nusantara Global, 2024)
This research is classroom action research (PTK) carried out in Class XI F 8 of SMA Negeri 6 Denpasar for the 2023/2024 academic year. This PTK aims to determine whether the implementation of the problem based learning method can improve the ability to understand the intrinsic elements of short stories and to find the right steps in implementing the problem based learning model to improve students' ability to understand the intrinsic elements of short stories. The data in this PTK is collected through observation methods and test methods. The collected data was then analyzed descriptively qualitatively and quantitatively. The research results showed that the students' initial test results reached an average score of 5.4, in the first cycle it increased to 6.7, until finally in the second cycle the students' average score increased to 8.05. The steps for the problem based learning model in understanding intrinsic elements are (1) group division, (2) the teacher provides lesson materials in the form of short story texts, (3) each group divides its members according to the questions contained in the text, (4) forming an expert group to discuss the topic in the questions they got, (5) expert group, returning to the original group, (6) presentation, (7) learning evaluation.